Characterization of Leaf Spot Pathogens from Several Spinach Production Areas in the United States - Liu, Bo (Plant disease, 2020)
Leaf spot diseases have become a major concern in spinach production in the United States. Determining the causal agents of leaf spots on spinach, their prevalence and pathogenicity, and fungicide efficacy against these pathogens is vital for effective disease management. Spinach leaves with leaf spots were collected from Texas, California, Arizona, and South Carolina from 2016 to 2018, incubated in a moist chamber, and plated on potato dextrose and tryptic soy agar media. Fungal and bacterial colonies recovered were identified based on morphology and sequence analysis of the internal transcribed spacer rDNA and 16S rRNA, respectively. Two predominant genera were isolated: (i) Colletotrichum spp., which were identified to species based on sequences of both introns of the glutamate synthetase (GS-I) and glyceraldehyde-3-phosphate dehydrogenase (gapdh-I) genes; and (ii) Stemphylium spp., identified to species based on sequences of the gapdh and calmodulin (cmdA) genes. Anthracnose (Colletotrichum spinaciae) and Stemphylium leaf spot (Stemphylium vesicarium and S. beticola) were the predominant diseases. Additional fungi recovered at very limited frequencies that were also pathogenic to spinach included Colletotrichum coccodes, C. truncatum, Cercospora beticola, and Myrothecium verrucaria. All of the bacterial isolates were not pathogenic on spinach. Pathogenicity tests showed that C. spinaciae, S. vesicarium, and S. beticola caused significant leaf damage. The fungicides Bravo WeatherStik (chlorothalonil), Dithane F-45 (mancozeb), Cabrio (pyraclostrobin), and Merivon (fluxapyroxad and pyraclostrobin) were highly effective at reducing leaf spot severity caused by an isolate of each of C. spinaciae and S. vesicarium, when inoculated individually and in combination